Changing body norms in the context of increasing body size: Samoa in 1995 and 2018. Issue 5 (4th February 2020) - To, Sophie B.; Brewis, Alexandra A.; Pomer, Alysa; Naseri, Take; Reupena, Muagututia S.; McGarvey, Stephen T.; Hawley, Nicola L.
Abstract: Objective: To understand how body size preferences changed in Samoa between 1995 and 2017 to 2019. Methods: Data were from adults aged from 31 to 59 years, who participated in two separate cross‐sectional studies of obesity and cardiometabolic risk conducted in Samoa in 1995 and 2017 to 2019. Participants nominated line drawings representing their current size, ideal size, the most attractive and healthiest size, and the lower/upper limits of "normal" size. Results: In both sexes, body size preferences and perceived current average body size have increased, yet preference for bodies smaller than one's perceived current size has persisted. Furthermore, the range of body sizes that people considered "normal" has narrowed, suggesting decreased tolerance for extremes of body size. Conclusions: These findings may have implications for mental and physical health outcomes, inform development of future health initiatives, and contribute to a deeper understanding of how body norms and weight‐related public health efforts interface.